Proposed Service Development for Expat Helper Indonesia - Putri Arfiandi, Nadira; Dhewanto, Wawan (The Indonesian Journal of Business Administration, 2017)
Abstract - Expat Helper Indonesia was established under PT. Manggala Daksa Raharja in 2015. Company provides one-stop service for expatriates who live in Indonesia. As a startup company, Expat Helper Indonesia is currently facing several issues. The main issues of this research are; the concept of one-stop solution has not proven yet, and the company performed ineffective service package sales. Author intends to conduct a deep research about service development and service package promotion. Qualitative method through literature review, observation and interview with 15 respondents are used to support the research. It started from analyzed the internal and external environment. Based on external analysis using Porter’s Five Forces framework indicates that company faces competition in the industry, although it’s indirect competition, but it still not lower the barrier for customers to switch providers, made company deals with the threat of substitute services and it consequences the bargaining power of buyer becomes high. For internal analysis, this research using VRIO analysis and STP analysis. The internal resource-based analysis resulted that company current level of competitiveness is in temporary competitive advantage. The output strategy formulation is demonstrated in validation board, a new proposed business model canvas and implementation plan. Validation board consists of 8 core assumptions, and 3 pivots. There are several additions in each basic block of the proposed business model canvas. The proposed implementation plan designed for 15 months period. One additional package was added in the new service package that represents the service development. Several strategies through online & offline marketing will used to gain brand awareness of the new service package.Keywords: Expatriate, Service Development, One-Stop Service